PTU-067 How are postoperative crohn's patients followed up? a retrospective analysis from a tertiary referral centre. (22nd June 2015) - O'connor, A; Taylor, J; Roberts, L; Scott, N; Carey, N; Ford, AC; Hamlin, PJ
Abstract : Introduction: Follow-up of patients resected for ileal Crohn's disease have shown that, in the absence of treatment, the post-operative recurrence rate is 70–90% within one year of the operation and 83–100% within 3 years. Prophylactic medication and disease monitoring has been proven to decrease the rate of clinical and endoscopic recurrence. Method: We performed a retrospective analysis by interrogating the pathology database over a five year period from 2009 to 2013 to identify cases and data was extracted by chart review and review of radiology and endoscopy databases to see how post-operative CD patients were being followed up. Results: Median follow-up period was 32 months (range 7 to 69). 55.9% of patients received followup with a gastroenterologist within three months and 78.9% are seen within 6 months. 7.9% did not see a medical gastroenterologist within 1 year of surgery. 2.63% were followed up long-term in the surgical clinic alone. 22.4% of patients had no endoscopic or radiologic evaluation of their disease ordered over the course of followup. 2.0% had investigations ordered that they repeatedly failed to attend. 65.8% of patients had imaging with 50% of all patients having an MRI. 42.8% of patients had colonoscopies. 33.6% of patients had both cross-sectional imaging and a colonoscopy. The mean duration to first cross-sectional abdominal post-operative imaging or lower GI endoscopy was 58 weeks with a median of 42 weeks (range 6 to 258). The first evaluation was symptom driven in 66.0% of cases and planned for routine disease staging 30.5% of the time. When investigation was symptom-driven the median interval post-op was 37 weeks compared to 48 weeks for planned followup. There was no influence for age or gender on how likely a patient was to receive follow-up, either planned or symptom driven. Conclusion: The proportion of patients returning to medical gastroenterology clinics in a timely manner after intestinal resection is suboptimal. Even among those who do return, disease staging is not routinely undertaken and is usually symptom driven within the first year after surgery and may well be clouded by factors such as post-operative pain, stoma function, anaemia and bile salt malabsorption. Post-operative follow-up and disease monitoring pathways could lead to improved care of postoperative CD patients. Disclosure of interest: None Declared.